A theory of the mesoscale organization of moist convection and the associated vertical momentum transport - Cheng, Anning, author; Randall, David A., advisor; Johnson, Richard H., committee member; Schubert, Wayne, committee member; Strauss, Steven H., committee member (Colorado State University. Libraries, 2001)
A parameterization of cumulus momentum transport is proposed. An important feature of the parameterization is the inclusion of the perturbation pressure-gradient force induced by interactions between the updraft and the environmental wind. The orientation, aspect ratio, phase speed and size of the organized convection are determined. These quantities depend on the vertical wind-shear and the stratification. GATE, ARM, EMEX, SCSMEX, and TOGA COARE data are used to test the theory. Results show that: 1) the predicted orientation, aspect ratio, and phase speed of organized convection agree well with the observations. 2) the vertical momentum transport is sensitive to the orientation of the cumulus clouds; 3) the momentum transport due to the perturbation pressure-gradient force tends to be upgradient and to cancel with the vertical momentum advection and detrainment effects. 4) the shear term produces positive convective kinetic energy (CKE), or negative CKE, depending on the vertical wind-shear and the velocity difference between the clouds and the environment; and 5) the CKE produced by shear accounts for about 1% of that by buoyancy, so its influence is very small in the cases studied here.
Keywords: atmosphere; environmental science